Transfusion of Resting Platelets Reduces Brain Hemorrhage After Intracerebral Hemorrhage and tPA-Induced Hemorrhage After Cerebral Ischemia - Luo, Haiyu; Wei, Lixiang; Lu, Lu; Kang, Lijing; Cao, Yongliang; Yang, Xing; Bai, Xiaofei; Fan, Wenying; Zhao, Bing-Qiao (Frontiers in Neuroscience, 2019)
Background: Exacerbated blood-brain barrier (BBB) damage is related with tissue plasminogen activator (tPA)-induced brain hemorrhage after stroke. Platelets have long been recognized as the cellular orchestrators of primary haemostasis. Recent studies have demonstrated further that platelets are required for supporting intact mature blood vessels and play a crucial role in maintaining vascular integrity during inflammation. Therefore, we sought to investigate whether platelets could reduce tPA-induced deterioration of cerebrovascular integrity and lead to less hemorrhagic transformation. Methods: Mice were subjected to models of collagenase-induced intracerebral hemorrhage (ICH) and transient middle cerebral artery (MCA) occlusion. After 2 hours of MCA occlusion, tPA (10 mg/kg) was administered as an intravenous bolus injection of 1 mg/kg followed by a 9 mg/kg infusion for 30 minutes. Immediately after tPA treatment, mice were transfused with platelets. Hemorrhagic volume, infarct size, neurological deficit, tight junction and basal membrane damages, endothelial cell apoptosis, and extravascular accumulation of circulating dextran and IgG, and Evans blue were quantified at 24 hours. Results: Platelet transfusion resulted in a significant decrease in hematoma volume after ICH. In mice after ischemia, tPA administration increased brain hemorrhage transformation and this was reversed by resting but not activated platelets. Consistent with this, we observed that tPA-induced brain hemorrhage was dramatically exacerbated in thrombocytopenic mice. Transfusion of resting platelets ameliorated tPA-induced loss of cerebrovascular integrity and reduced extravascular accumulation of circulating serum proteins and Evans blue, associated with improved neurological functions after ischemia. No changes were found for infarct volume. Inhibition of platelet receptor glycoprotein VI (GPVI) blunted the ability of platelets to attenuate tPA-induced BBB disruption and hemorrhage after ischemia. Conclusions: Our findings demonstrate the importance of platelets in safeguarding BBB integrity and suggest that transfusion of resting platelets may be useful to improve the safety of tPA thrombolysis in ischemic stroke.